TINGKAT PELAYANAN (LOS) PADA RUAS JALAN PERKOTAAN TANJUNG REDEB KABUPATEN BERAU Studi Kasus: Simpang Empat Simpang 4 Jalan Durian II-Jalan Durian III-Jalan Pulau Panjang (Depan RS)-Jalan Pulau Panjang: TINGKAT PELAYANAN (LOS) PADA RUAS JALAN PERKOTAAN TANJUNG REDEB KABUPATEN BERAU Studi Kasus: Simpang Empat Simpang 4 Jalan Durian II-Jalan Durian III-Jalan Pulau Panjang (Depan RS)-Jalan Pulau Panjang - Agista Aristia Arini (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
Kabupaten Berau has potential in the tourism and coal mining sectors, which have an impact on high growth population and economic increase rapidly every year. High population mobility can measured by the increasing need for daily living. This activity also indirectly requires the availability of transportation access. Data shows that vehicle ownership in Berau Regency increased by 63,456 units from 2018 to 2021 (BPS, 2022). Level of services (LOS) is a measure of the performance of a road section or intersection Level of Service is a part and frequently used term and concept of transportation planning in urban planning, which is calculated based on the level of road use, speed, density and obstacles that occur. In quantitative analysis, the level of road service is shown by Q/C (Q = traffic volume, C = road capacity). In conclusion, on several urban roads in Tanjung Redeb there are still no serious transportation problems found, it's just that problems occur only because of inappropriate traffic management or transportation arrangements.